Childbirth knowledge, beliefs and practices among aetas in Pampanga - Alegre, Diana Gloria D.
Women are the focus of major health programs of the Department of Health and yet the trend in maternal mortality rates continue to increase alarmingly through the years. Mainstream women remain in the marginalized sector and their indigenous counterpart also remain among the poorest and marginalized sectors in the country. The need for understanding the indigenous women's cultural context, their concerns and health needs will continue as a challenge among health workers tasked to serve them.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Birth customs; Childbirth